KAIJUTITAN MAUI, A SAUROPOD TITANOSAUR FROM THE UPPER CRETACEOUS (SIERRA BARROSA FORMATION, NEUQUÉN BASIN) OF NORTHERN PATAGONIA ARGENTINA: HISTOLOGICAL AND TAPHONOMIC CONSIDERATIONS - Leonardo Sebastián Filippi; Elena Previtera; Alberto Carlos Garrido (Publicación Electrónica de la Asociación Paleontológica Argentina, 2024)
Kaijutitan maui is a basal titanosaur from the Sierra Barrosa Formation (Coniacian, Upper Cretaceous), Neuquén Basin, Patagonia Argentina. The Neuquén Basin in northwestern Patagonia, Argentina, holds the most important record of Cretaceous dinosaurs from South America. This work constitutes the first case of taphonomic and histological study of a dinosaur from the Rincón de los Sauces area. Kaijutitan is represented by cranial and postcranial materials of an adult individual of huge body size, preserved in clay sediments related to a floodplain environment. Bones were found disarticulated but associated, largely respecting their relative anatomical position. histological and diagenetic features of bones were analyzed in order to interpret the alteration degree of bone microstructure. Biostratinomic processes inferred are subaerial biodegradation, disarticulation, preburial weathering (cracking and flacking), and abrasion. Fossil-diagenetic processes comprise compaction, deformation, permineralization, and fracturing. Permineralization stages included infilling of bone cavities and fractures with sediments, iron oxides, calcite, or an iron oxide-calcite association during the burial history. Some characteristics suggest that the Kaijutitan specimen suffered weathering for a certain period of time before final burial and that biological activity in the carcass acted as a dispersal agent for the bones within the paleontological site.